The Effect of Service Quality, Price Policy and Customer Satisfaction on Consumer Loyalty Star Fitness Center Palembang City - Kristina, Putri Cicilia; Riyoko, Endie; Daryono, Daryono; Iswana, Bayu (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This research is motivated by the rapid development of business in the fitness industry, one of which is the star fitness center Palembang City which is one of the fitness centers that are in great demand by the public. Therefore, the purpose of this study is to identify the extent to which service quality, price policy, customer satisfaction at Star Fitness Center contribute to consumer loyalty. The type of research used is a type of quantitative research. This research instrument uses Likert scale. Data collection techniques using questionnaires. Hypothesis testing using F test and t test. The results showed that the price policy variable (X2) had the greatest influence on interest in purchasing Star Fitness Center Palembang products. This can be shown from the value of the Standardized Coefficient Beta on the t test of 0.444. In addition to customer satisfaction, price policy is a variable that can be controlled and decide whether a product Star Fitness Center Palembang City can be accepted or not.